Insulin Sensitivity Assessed by Stable Isotopes with Oral Glucose Administration: Validation with Euglycaemic Clamp. (3rd November 2013) - Bluck, Leslie; Williams, Rachel; Jackson, Sarah; Salgin, Burak; Acerini, Carlo; Dunger, David
Abstract : Methods of determining insulin sensitivity that use an oral challenge of glucose are preferred to those using intravenous administration since the measurement is made in conditions more akin to normal physiology. One previously reported protocol (ODILE) studies glucose uptake in isolation from absorption and endogenous production by the intravenous administration of tracer approximately forty-five minutes after the oral dose is given. However, this methodology has not been validated against other accredited procedures. This study utilizes the euglycemic hyperinsulinemic clamp in order to validate the ODILE method.